DIFFERENCES IN SOME MORPHOLOGICAL CHARACTERISTICS AND THIGH MUSCLE FORCE OF BOUNCE LEG BETWEEN FOOTBALL PLAYERS AND GOALKEEPERS - Živko Kalentić; Dragana Golik-Perić; Nenad Sudarov; Vojin Jovančević (Exercise and Quality of Life)
The aim of this study is to determine the differences in certain morphologicalcharacteristics and thigh muscle force of bounce leg between football players andgoalkeepers. The examined group consisted of 15 goalkeepers and 14 players, aged 15 ñ 18years, from Vojvodina cadet league. Five parameters were tested by means of isokineticdynamometer, and 6 morphological factors were measured. The differences between subsamples were gained by multivariable and univariable analysis of variance. Multivariableanalysis was used to determine significant difference at the level (p =.00), and we determinedstatistically significant difference on individual basis in body height and in muscle masspercentage. Almost equal results in thigh muscle force of bounce leg among the subjects andno difference in other variables can be explained by identical training process for players andgoalkeepers. The data gathered demonstrate that in the future it will be necessary toimplement different training process, specially designed for goalkeepers.